دور الإدارة المدرسية في مواجهة مشكلة التأخر الدراسي في الطور الإبتدائي - دبار, عائشة; هرشة, منى (جامعة الوادي university of Eloued, 2015)
Summary of the study -This stady gims at defining the role of the school a dministration in fighting the problem of chool failure . It started from a major question: -"that is the the contribution of the school administration in solving the problem of school failure?". This primary question leads to three sul – questions : -Wat is the role of prinary chools directors concerning the problem ? To which extent are consolidation courses supervised by the administration successful ? Wat are the proposals and solution suggested by the administration to solve the problem ? -we relied on the strategy of description and analyses . -The study was berformed on a primary schools sample in EL-oued of about 50 headmas ters. We used intervieuring and conversations , it was done at random and consisted of 32 questions ,the findings were as folouvs : -Charts (06) ,(07),(08),(09) confirmed that headmasters ought to undergo a major role in fighting this issue . -From (17) , (18) , (19) ,(21) ,(26) ,confirmed that Consolidation courses are becoming a necessity . -It's confirmed from charts (30) , (31) , (32) , the solisions and proposals
دراسة ميدانية في بعض إبتدائيات الوادي
مذكرة ماستر في علم الاجتماع تخصص علم اجتماع التربية
Keywords: الإدارة المدرسية، التأخر الدراسي، المدرسة الإبتدائية الجزائرية; Administration scolaire, retard scolaire, école primaire algérienne; School administration, school delay, Algerian primary school